Water-Flow Protection to Protected Areas in Nepal - Poudel, Krishna Prasad (Tribhuvan University Journal, 2010)
Available with Full text.Key words: Streams and Rivers; Water-flow; Wild-Life Conservation; NepalTribhuvan University Journal Vol. XIX, 1996 Page: 49-57 Uploaded Date: 24 Nov., 2010